PERAN COOPERATIVE LEARNING DALAM MENDUKUNG PENDIDIKAN INKLUSI DI SEKOLAH DASAR - Shifa, Nabilla Nur; Suardi, Laxmi Permata Sari; Nurmaliya, Intan; Fauziah, Risti; Amalia, Mutiara Citra (Jurnal Merah Putih Sekolah Dasar, 2025)
Inclusive education aims to ensure that all students, including those with special needs, have equal opportunities to learn in a normal classroom environment. However, there are still some challenges to overcome in implementing it at the primary education level. The most important thing is a learning strategy that can accommodate the diverse characteristics of students. The purpose of this study is to evaluate the collaborative learning role in supporting inclusive education in elementary schools, specifically in terms of improving student learning outcomes and social interaction. A qualitative descriptive approach was used in this study. Data was collected from books, scientific journals, and relevant academic sources on inclusive education and cooperative learning strategies. The results show that cooperative learning strategies such as Jigsaw, Two Stay Two Stray (TSTS), STAD, and Think-Pair Share are effective in promoting participation, cooperation, and positive social interaction in inclusive classrooms. Cooperative Learning remains a relevant and effective approach if supported by proper planning and teacher ability. However, there are issues such as a lack of learning time and teacher readiness to manage the classroom. Therefore, cooperative learning can be considered a beneficial strategy for creating an inclusive, collaborative, and equitable learning environment in elementary schools.